Kebijakan Publik Menyangkut Pendidikan dan Kesetaraan Gender - Harist Hafiid; Budi Harsono; Bibit Santoso (Public Administration Journal (PAJ), 2017)
Promoting gender equality is a major part of the development strategy in order to empower the community. Education has a role to play in providing an opportunity to rectify gender inequality. Gender mainstreaming in education is intended to ensure that policies, programs and educational activities provide opportunities and benefits the same for girls and boys. Education is very important for the empowerment of women. Education allows girls and boys participate in social life, economy, and politics. Achieve equality in learning opportunities and achievement of learning outcomes for men and women is a major challenge.